The Synthesis of V2O3 Nanorings by Hydrothermal Process as an Efficient Electrocatalyst Toward N2 Fixation to NH3 - Wang, Ning; Song, Qing-Song; Liu, Wen-Jing; Zhang, Jian (Frontiers in Energy Research, 2020)
A new ringlike V2O3 architecture was successfully synthesized by a template-free hydrothermal method, and the sulfur ions-assisted central-etching mechanism of the ringlike structure was proposed. Herein, as a proof-of-concept experiment, taking V2O3 nanorings as non-noble-metal-free nitrogen reduction reaction (NRR) catalysts, they show desired electrocatalytic performance toward NRR under ambient conditions (maximum yield: 47.2 µg h−1 mgcat.−1 at −0.6 V vs. reversible hydrogen electrode, maximum Faraday efficiency: 12.5% at −0.5 V vs. reversible hydrogen electrode), which is significantly higher than those of noble metal-based catalysts.